2003
DOI: 10.1289/ehp.5592
|View full text |Cite
|
Sign up to set email alerts
|

Maternal blood lead concentration, diet during pregnancy, and anthropometry predict neonatal blood lead in a socioeconomically disadvantaged population.

Abstract: To determine the influences of maternal diet and nutrition during pregnancy on the blood lead level of neonates, we conducted a study of mother-infant pairs from lower socioeconomic circumstances living in Albany County, New York. Maternal blood lead (MBPb), anthropometry, and diet were assessed in each trimester. Neonates' blood lead (NBPb) levels were low (geometric mean = 1.58 micro g/dL), and none had elevated blood lead. More than 50% of the mothers had intakes below the recommended dietary allowances for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 58 publications
6
55
3
Order By: Relevance
“…Between 20 weeks of gestation and delivery, blood lead increased by 1.6 g/dl. This U-shaped pattern of change in blood lead level over pregnancy is consistently observed Schell et al, 2000Schell et al, , 2003Sowers et al, 2002;Gulson et al, 2004). Plasma lead level appears to follow a similar pattern (Tellez-Rojo et al, 2004).…”
Section: Kinetics Of Lead During Pregnancy and Lactationsupporting
confidence: 56%
“…Between 20 weeks of gestation and delivery, blood lead increased by 1.6 g/dl. This U-shaped pattern of change in blood lead level over pregnancy is consistently observed Schell et al, 2000Schell et al, , 2003Sowers et al, 2002;Gulson et al, 2004). Plasma lead level appears to follow a similar pattern (Tellez-Rojo et al, 2004).…”
Section: Kinetics Of Lead During Pregnancy and Lactationsupporting
confidence: 56%
“…[39][40][41][42] At this stage, the possibility of further exposure to lead after birth, especially in socioeconomically disadvantaged populations, not only in South Africa but also in other developing countries, cannot be ruled out. 43 In contrast to cadmium, mercury and lead discussed above, manganese is an essential trace metal and both deficiency and excess of manganese are toxic to humans. Like lead and mercury, manganese is a neurotoxic metal able to easily cross the bloodbrain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Children who were Fe-deficient and were living in environments containing high levels of Pb 2+ had higher blood Pb 2+ concentrations than children whose iron levels were normal (Brandman et al, 2001). Furthermore, Schell et al (2003) found that the blood levels of Pb 2+ in newborns were related inversely to the Fe status of the mothers. Owing to the observed interaction between Fe 2+ and Pb 2+ , it can be hypothesized that these two metals utilize one or more of the same transport mechanisms, perhaps the Fe 2+ transporter, DMT1.…”
Section: Leadmentioning
confidence: 92%
“…Specifically, the toxicological signs of Pb 2+ exposure, such as the urinary excretion of δ-aminolevulinic acid, were greater in rats fed an Fe-deficient diet than in rats fed a normal diet (Six and Goyer, 1972). Epidemiological studies of children have demonstrated a relationship between Fe status and blood levels of Pb 2+ (Brandman et al, 2001;Schell et al, 2003). Children who were Fe-deficient and were living in environments containing high levels of Pb 2+ had higher blood Pb 2+ concentrations than children whose iron levels were normal (Brandman et al, 2001).…”
Section: Leadmentioning
confidence: 99%